Cometabolic Degradation of Dibenzofuran by Biphenyl-Cultivated Ralstonia sp. Strain SBUG 290 - Becher, Dörte (American Society for Microbiology, 2000)
Cells of the gram-negative bacterium Ralstonia sp. strain SBUG 290 grown in the presence of biphenyl are able to cooxidize dibenzofuran which has been 1,2-hydroxylated. Meta cleavage of the 1,2-dihydroxydibenzofuran between carbon atoms 1 and 9b produced 2-hydroxy-4-(3′-oxo-3′H-benzofuran-2′-yliden)but-2-enoic acid, which was degraded completely via salicylic acid. The presence of these intermediates indicates a degradation mechanism for dibenzofuran via lateral dioxygenation by Ralstonia sp. strain SBUG 290.